Implementation of Strategic Management in Improving Quality and Graduate Outcomes - Afifah, Umi; Lian, Bukman; Putra, Muhammad Juliansyah (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This qualitative study explored strategic management implementation at Junior High School Negeri 12 Palembang to enhance education quality and graduate outcomes. Using descriptive research methods, the data were collected through observations (November 19-29, 2024), interviews with 12 stakeholders, and document analysis. The study identifies four key strategic elements: organizational structure, leadership, culture, and reward systems. Findings reveal that while the school has implemented comprehensive strategies including teacher training programs and extracurricular development, challenges remain in resource allocation and technology integration. The study contributes to educational management literature by demonstrating how strategic alignment between these elements can improve institutional performance in Indonesian public schools.